WEB-BASED CAT FOOD RECOMMENDATION SYSTEM USING COLLABORATIVE FILTERING METHOD - Barus, Laila Tusyfa; Dewi, Arie Rafika; Lubis, Fachrul Rozi (Cattleya Darmaya Fortuna, 2025)
Cats are a type of mammal that is popular and widely kept as a favorite pet among the wider community, certainly cat owners want to provide the best quality for their pets, one of the most important of which is cat food. The large selection of types of cat food in modern times makes many cat owners feel confused in choosing cat food that is suitable for their pets. Therefore, a system is needed to provide recommendations for cat owners in determining the type of cat food for their pets. The creation of this system uses the collaborative filtering method, where this method is used to find out recommended food products based on the rating data that has been collected. This system was developed using PHP programming language and MySQL database and using Laravel framework. With this system can help cat owners get information about cat food products and with collaborative filtering can make it easier for cat owners to find out which food products are recommended from highest to lowest.